Optimizing Zakat Distribution: An Examination of Poverty, Income, and Unemployment in Kudus City - Rahmawati, Ira Ayuk; Qomar, Moh. Nurul (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2024)
This study explores the optimization of zakat distribution in Kudus City, focusing on the effects of poverty, income, and unemployment. Employing a quantitative research method and the analysis of secondary data, this investigation employs EViews 10 for the examination of pertinent variables. Results from Kudus City indicate that the